The Experience of Nurses Transitioning to Primary Nursing in Indonesia: A Hermeneutic Phenomenological Study - Rantung, Gilny Aileen Joan; Sitanggang, Septyarani (Journal of Applied Nursing and Health, 2025)
Background: Primary nursing is promoted globally for better continuity, accountability, and engagement,, butthere is limitede is limited evidence from Indonesia on nurses' transition from team to primary care. This study explored the lived experiences of nurses transitioning from team nursing to primary nursing in Indonesia, aiming to understand how they adapt, the barriers they encounter, and the impact of this shift on nurse–patient relationships. Methods: A qualitative approach was used, employing Van Manen’s hermeneutic phenomenology. Ten registered nurses working in medical–surgical wards of a tertiary hospital in Bandung, Indonesia, were purposively sampled. Inclusion criteria included registered nurses with experience in both team and primary nursing models. Nurses in managerial roles without bedside duties were excluded. Data were collected through in-depth semi-structured interviews lasting 45–60 minutes, conducted face-to-face or via secure online platforms. These interviews were audio-recorded, transcribed verbatim, and member-checked. Analysis followed Van Manen’s reflective approach, with thematic analysis supported by NVivo (QSR International, version 12) for data organization. Trustworthiness was maintained through audit trails, reflexivity, peer debriefing, and thick description. Ethical approval was obtained (No. 513/KEPK-FIK.UNAI/EC/VI/25). Reporting followed COREQ. Results: Three themes emerged: (1) Readiness and adaptation to change, where nurses emphasized mindset and gradual learning as essential to adaptation; (2) Challenges in practice and system limitations, including high nurse-to-patient ratios, administrative burden, delayed support services, and training misaligned with practice; and (3) Strengthened nurse–patient relationships, reflecting improved trust, openness, and professional accountability, which sustained motivation despite systemic barriers. Conclusion: This study reveals how Indonesian nurses manage transitioning to primary nursing. Despite systemic challenges that affect continuity and workload, nurses' commitment and strong patient ties sustain their efforts. The findings highlight the importance of aligning training with practice, improving staffing ratios, and ensuring consistent patient assignments to support primary nursing